El poblamiento rural romano en torno a la ciudad de cara. Las comunicaciones y la influencia en su formación - Calonge Miranda, Adrián; Santos Yanguas, Juan (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2017)
In this paper we consider the different factors that influenced the formation of the network of Villae around the Cara civitas. They have been related rivers as lines of communication, the roman roads, the civitas itself and the location of the Villae.